Violência de gênero e direitos humanos: um estudo do atendimento dos crimes de violência doméstica e familiar contra a mulher na 1ª DEAM de Goiânia (2010-2023) - Alves, Glauco Leão Ferreira (2024)
Women who are victims of gender-based violence need public policies so that basic human rights are actually implemented. In this way, the objective was to bring to the academic debate the assistance, which occurred between 2010 and 2023, to crimes of domestic and family violence at the 1st Specialized Police Station for Women's Assistance in Goiânia - DEAM, based on discursive textual analysis about the feelings, anxieties, limitations and dilemmas of the civil police officers from this police station. Based on the research entitled Public Security Agents as Subjects of Rights, from the Human Rights Center of the Federal University of Goiás, a questionnaire was applied, in 2023, to 22 professionals who work or worked at this police station: agents, clerks, delegates and psychologists, in a quantitative-qualitative approach. In relation to the theoretical framework that supported this thesis, the theme of violence was approached, from an interdisciplinary perspective, consolidating the importance of the role of the street-level bureaucrat as an agent for transforming an unequal, sexist, violent and prejudiced reality. In this sense, data analysis demonstrated the need for constant training of these civil police officers who are on the front line in the fight against violations of women's rights. The training we are talking about must focus on gender relations and social markers of difference, because it was also noted that there is little institutional appreciation for the police officers who are assigned to this police unit. It is essential to pay attention to the mental health of these professionals who deal with violence on a daily basis and who support a workload increased by the low police force. The lack of motivation and illness of these police officers, who at certain times, see themselves more as subjects of duties than of rights, can negatively reflect on the care provided to victims at DEAM, in contrast to the reason for the existence of this police station: to empower women to break the cycle of violence.